Simultaneous determination of squalene, tocopherols and phytosterols in edible vegetable oil by SPE combined with saponification and GC-MS. (1st November 2022) - Wu, Limei; Zhao, Jingjing; Wu, Lihua; Zhang, Yuhuan; Li, Jianke
Abstract: A method for simultaneous determination of 14 functional components of squalene, tocopherols and phytosterols in edible oil was established based on solid phase extraction (SPE), saponification and gas chromatography-mass spectrometry (GC-MS). Depending on the characteristic ions of the target substances, 14 compounds were well separated in 20 min. The limit of detections (LOD) and the limit of quantifications (LOQ) were in the range of 0.010–0.050 and 0.033–0.167 μg/mL, respectively. Method validation showed linearity of calibration curves (α = 0.05) with the recoveries at three spiked levels between 91.29 and 111.93%. The relative standard deviation (RSD) of intra-day and inter-day precisions were less than 6.11%. The results derived from the established method demonstrated a wide variation of detected compounds in 15 kinds of common edible vegetable oils. The proposed SPE combined with saponification and GC-MS provides a rapid and simple method for the simultaneous determination of the functional compounds in oils and detection of the adulterated vegetable oil. Graphical abstract: Image 1 Highlights: Simultaneous analysis of fourteen functional lipophilic compounds in 20 min was purposed. Squalene, tocols and phytosterols in fifteen vegetable oils were identified. SPE combined with saponification were used to extract targets from oil.